An ‘abyss of self-love’ - Carla Zdanow; Bianca Wright (Communicare)
Narcissism is increasingly being regarded as one of the most serious sociocultural problems of the contemporary era. Indeed, recent studies by Baldwin and Stroman (2007) and Buffardi and Campbell (2008), among others, have advanced the opinion that new media technologies – particularly social networking websites – have significantly exacerbated the rise and spread of narcissism in contemporary society. Based on this premise that social media provide the perfect platform for the promotion of self-infatuation, this research paper provides a critical analysis of the potential influence of social media in the development of a widespread narcissistic sociocultural condition. In this regard, claims that increasingly consumerist, individualist and media-saturated societies are nurturing a culture of extreme narcissism, vanity and entitlement are examined in relation to an increase in the use of consumer-orientated new media technologies. In particular, by examining the structural components of the popular social networking site, Facebook, this research highlights the connection between the use of this form of new media and the engenderment of an acutely consumerist and narcissistic subjectivity. That is, the role of new media technologies in the promotion of narcissistic identity construction is examined as a factor of particular significance in the formation of contemporary subjectivity. In relation to this, the impact of online narcissism on the perpetuation and propagation of capitalist isolation, alienation and insecurity is investigated before some remedial measures ‒ which co-opt rather than negate such social media ‒ are proposed.